Beyond Dutch borders : transnational politics among colonial migrants, guest workers and the second generation - Mügge, Liza (2010)
Despite widespread scepticism in receiving societies, migrants often remain loyal to their former homeland and stay active in the politics there. Beyond Dutch Borders is about such ties. Combining extensive fieldwork with quantitative data, this book compares how transnational political involvement among guest workers from Turkey and post-colonial migrants from Surinam living in the Netherlands has evolved over the past half-century. It looks at Turks seeking to improve their position in Dutch society, Kurds lobbying for equal rights in Turkey and Surinamese hoping to boost development in their country of origin. Sending-state governments, political parties and organisations are shown to be key shapers of transnational migrant politics both in opposition to, and support of, homeland ruling elites. Meanwhile, it becomes clear that migrants' border-crossing loyalties and engagement have not dented their political integration in the receiving societies - quite the opposite. Certainly in this respect, the sceptics have been wrong.